2015
DOI: 10.3758/s13414-015-0843-3
|View full text |Cite
|
Sign up to set email alerts
|

Does perceptual confidence facilitate cognitive control?

Abstract: Our visual perception is typically accompanied by a sense of subjective confidence. Since perceptual confidence is related to prefrontal activity, higher perceptual confidence may enhance cognitive control functions. To examine this interaction, we developed a novel method to selectively manipulate perceptual confidence while keeping stimulus discrimination accuracy constant. In a behavioral experiment, grating stimuli with different orientations were presented as go/no-go signals. Surprisingly, the results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
199
2
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(230 citation statements)
references
References 35 publications
27
199
2
2
Order By: Relevance
“…1). Whereas this has been empirically demonstrated through manipulations of stimulus evidence (Koizumi et al, 2015; Samaha, Barrett, et al, 2016; Zylberberg et al, 2014), we show that this is the case when internal evidence fluctuates spontaneously as a function of cortical excitability, as indexed by prestimulus alpha power.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…1). Whereas this has been empirically demonstrated through manipulations of stimulus evidence (Koizumi et al, 2015; Samaha, Barrett, et al, 2016; Zylberberg et al, 2014), we show that this is the case when internal evidence fluctuates spontaneously as a function of cortical excitability, as indexed by prestimulus alpha power.…”
Section: Discussionmentioning
confidence: 47%
“…Their findings show that, whereas choice accuracy was determined by relative difference in luminance between the two stimuli, confidence was insensitive to fluctuations in luminance for the non-chosen stimulus but was driven by the absolute luminance of the chosen stimulus. Subsequent work found that proportionally increasing the contrast of a target as well as the contrast of noise (or a non-target, e.g., Koizumi, Maniscalco, & Lau, 2015; Expt 1A) led to increased confidence despite no change to accuracy (Koizumi et al, 2015; Samaha, Barrett, Sheldon, LaRocque, & Postle, 2016). Here, we measured prestimulus alpha power as a trial-by-trial index of cortical excitability while observers judged the orientation of a grating and provided subjective confidence ratings.…”
Section: Introductionmentioning
confidence: 99%
“…Introducing these normative constraints into models of metacognition is an important goal for future work. For instance, it would be of interest to explore whether differential sensitivity to evidence for or against a choice (Koizumi et al, 2015; Maniscalco et al, 2016; Zylberberg et al, 2012), and differential effects of attention on performance and confidence (Rahnev et al, 2011; Solovey et al, 2015) could be accommodated in a Bayesian framework with appropriate constraints. The current framework may also provide a benchmark from which to assess other apparent suboptimalities in confidence that are normative when appropriate computational considerations are taken into account (e.g., the effects of actions on subsequent confidence ratings).…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies also adopt a normative approach and define confidence in close association with the strength of the internal perceptual signal11, several studies suggest that confidence and perceptual performance can be dissociated91516171819. For example, applying transcranial magnetic stimulation (TMS) to the prefrontal cortex (PFC) resulted in a change in confidence reports without changing task performance9.…”
mentioning
confidence: 99%